HIFEMA TRAUMATIK - Hondrizal; Alimurdianis (Journal of Public Health Indonesian, 2025)
Traumatic hyphema is an ophthalmological condition resulting from bleeding in the anterior chamber, generally caused by blunt trauma to the eyeball. This condition can cause decreased visual acuity and carries the risk of serious complications such as secondary glaucoma, corneal staining, and optic atrophy if not treated promptly and appropriately. This paper aims to provide a comprehensive understanding of traumatic hyphema, including its etiology, pathophysiology, classification, clinical manifestations, diagnosis, management, and potential complications. The method used is a descriptive study through a literature approach and clinical observation during the clerkship at the Department of Ophthalmology, M. Natsir Solok Regional General Hospital. Data were obtained from a literature review and direct observation of patients. The results indicate that hyphema is most often experienced by adolescent boys and is characterized by decreased visual acuity, pain, and blood accumulation in the anterior chamber. The diagnosis is confirmed through anamnesis, visual acuity examination, and evaluation of intraocular pressure. Management is conservative, and surgery is required in severe cases or cases accompanied by complications. Early treatment is crucial to prevent further complications. Therefore, good clinical understanding and early detection are key to improving the prognosis of patients with traumatic hyphema.